Impact of HLA-G in the outcome of vitiligo in Tunisian patients - Jalel Akrem; Ridha Aouadi; Laurent Duboisier; Philippe Moureaux; Hamdaoui M (Wolters Kluwer Medknow Publications, 2010)
Background: The human leukocyte antigen (HLA) system in the skin coordinates the pigmentation and immune response and could be implicated in the pathogenesis of vitiligo. Human leukocyte antigen HLA-G is a nonclassic, major histocompatibility complex class I molecule expressed in the extravillous cytotrophoblast at the feto-maternal interface. It is known to protect the fetus from maternal cellular immunity. Analogically, it could be implicated in the pathogenesis of autoimmune diseases such as vitiligo. Aims: To compare the expression of HLA-G between vitiligo patients and healthy controls. Materials and Methods: In the present study, 22 vitiligo patients and 24 healthy controls were investigated to look for a possible correlation between HLA-G expression and this pathology. Expression of HLA-G in cutaneous biopsy specimens was investigated by immunohistochemical analysis. Results: HLA-G was detected in the biopsy specimens of 3 (13%) out of 22 patients. This number was significantly higher in healthy controls 18 (75%) out of 24 as compared to vitiligo patients ( P < 0.001). Conclusion: There is significant negative correlation between HLA-G expression and vitiligo. In our mind, upregulation of HLA-G expression in lesional skin could be local (superficial expression) or systemic (soluble HLA-G isoforms) compensation to restore normal pigmentation in lesions.